Differences in Average Albumin Levels in Coronavirus Disease 2019 (COVID-19) Survivor and Non-Survivor Patients: A Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Atrya, Doan; Rikarni; Elvira Yusri (HM Publisher, 2024)
Background: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 infection triggers a systemic inflammatory response that can lead to a decrease in serum albumin levels. A more severe inflammatory response in non-survivor COVID-19 patients may correlate with a more significant decrease in albumin levels. This study aims to analyze differences in mean albumin levels in COVID-19 survivors and non-survivors. Methods: This cross-sectional analytical study involved 40 COVID-19 survivors and non-survivors treated at Dr. M. Djamil General Hospital Padang from July 2021 to September 2021. Serum albumin levels were checked using an automated clinical chemistry tool. Data analysis was carried out using the Mann-Whitney non-parametric test, with a significance level of p < 0.05. Results: The mean age of the study subjects was 49.4 (16.3) years, with the majority of cases occurring in men (67.5%). The median albumin levels in all COVID-19 patients, COVID-19 survivors, and COVID-19 non-survivors were 3.2 (2.20–5.00) g/dL, respectively; 4.1 (3.0–5.0) g/dL; and 2.9 (2.20–3.70) g/dL (p = 0.001). Conclusion: There is a significant difference in mean albumin levels between COVID-19 survivors and non-survivors. Lower albumin levels were found in non-survivor patients. Albumin can be a potential biomarker for predicting clinical outcomes of COVID-19 patients.